Interfacial effects on lithium-ion diffusion in two-dimensional lateral black phosphorus–graphene heterostructures. Issue 9 (16th February 2023) - Cheng, Liyuan; Ge, Mei; Chen, Jiali; Zhang, Junfeng
Abstract : Li-ion diffusion depends on the atomic details of interface in two-dimensional lateral black phosphorus–graphene heterostructures. Abstract : Lateral heterostructures constructed from different two-dimensional (2D) materials can be potentially used in lithium-ion batteries (LIBs). The interface between two different components strongly affects LIB charge and discharge processes. Herein, the atomic structures, electronic properties, and Li-ion diffusion characteristics of lateral black phosphorus–graphene (BP–G) heterostructures are studied via first-principles calculations. The obtained results reveal that BP–G heterostructures with either zigzag (ZZ) or misoriented interfaces constructed according to Clar's rule possess a small number of interfacial states and are electronically stable. Furthermore, compared with the perfect ZZ interface of BP–G, Clar's interfaces provide a larger number of diffusion paths with much lower energy barriers. The findings of this study suggest that lateral BP–G heterostructures can provide insights for rapid charge and discharge processes in LIBs.